When it was grand the radical Republican history of the Civil War - Keith, LeeAnna (Hill and Wang, a division of Farrar, Straus and Giroux, 2020)
"A history of antiracist and abolitionist activism in the Civil War-era Republican Party"--
Keywords: Republican Party -- USA; Abolitionismus; Sezessionskrieg -- 1861-1865; Republican Party (U.S. : 1854- ) / History / 19th century; Political parties / United States / History / 19th century; Antislavery movements / United States / History / 19th century; Radicalism / United States / History / 19th century; African Americans / Politics and government / 19th century; African Americans / Civil rights / History / 19th century; United States / Politics and government / 1849-1877; United States / History / Civil War, 1861-1865; Republican Party (U.S. : 1854- ); African Americans / Civil rights; African Americans / Politics and government; Antislavery movements; Political parties; Politics and government; Radicalism; United States; 1800-1899; History